ANALYSIS OF TYPES AND ABUNDANCE OF SOLID DOMESTIC WASTE IN THE COASTAL TOURIST AREA OF DUMAI CITY - Pramukti, Masdhuki; Nedi, Syahril; Amin, Bintal (Lembaga Penelitian dan Pengabdian Kepada Masyarakat Universitas Riau, 2024)
The coastal areas of Dumai City in Riau Province are rapidly developing regions, especially in the tourism sector. This city offers several attractive beach destinations, such as Pasir Koneng Beach, Beringin Indah Beach, and Purnama Beach, attracting many local and international tourists. However, tourism growth in Dumai City also leads to an increase in solid domestic waste, which can threaten the coastal environment and the sustainability of marine ecosystems. This research aims to analyze the types and abundance of solid domestic waste in the coastal tourism areas of Dumai City. Through direct survey methods and descriptive analysis, samples of solid domestic waste were collected from three different beach locations: Purnama Beach, Koneng Beach, and Beringin Indah Beach. The results show that plastic waste is the most dominant type in all research locations, followed by wood and Styrofoam. Analysis of solid domestic waste's mass density and abundance indicates no significant difference between sampling stations or sampling times. This study provides a better understanding of the solid domestic waste issue in the coastal areas of Dumai City. It emphasizes the need for more effective management actions to maintain the sustainability of coastal tourism environments and prevent negative impacts on marine ecosystems and human well-being.